False confessions among suspects in police custody: Implications of anxiety and perceived stress - Okoka, Happiness; Kheswa, Jabulani Gilford (Nurture, 2024)
Purpose: The purpose of the study was to examine the effect of anxiety and stress on false confessions among police suspects in custody. Design/Methodology/Approach: The study adopted an ex post facto design. Participants were one hundred and nine (N 109) suspects in custody at the State Criminal Investigation Department of Kaduna State Police Command, Kaduna State, Nigeria. The present study included three measurement tools to assess different constructs: The Gudjonsson Confession Questionnaire-Revised (GCQ-R) was utilized to evaluate false confession, the State-Trait Anxiety Inventory (STAI) was employed to assess anxiety levels, and the Perceived Stress Scale (PSS) was utilized to measure perceived stress. Findings: Results revealed that state anxiety positively predicted false confession (β =0.191, p < 0.05), whereas trait anxiety has no significant effect on false confession (β=- 0.050, p > 0.05), while perceived stress positively predicted false confession (β =0.273, p < 0.05). Conclusion: The study concluded that state anxiety and perceived stress contribute to a suspect’s predisposition to make a false confession. It was recommended that police officers be more cognizant of when and under what conditions they use interrogation methods in view of the level of anxiety and stress the suspect might be in.